2017
DOI: 10.14735/amko2017182
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Melanoma – from Classical Histology towards Molecular Genetic Testing

Abstract: This article summarizes information on the correlation of morphological findings with genetic changes, discusses the representation of individual genetic types in various morphological subgroups and deals with the newly proposed genetic classification of melanoma and the current possibilities, pitfalls and challenges in BRAF testing of malignant melanoma. It also describes the current testing situation in the Czech Republic - the methods used, the representation of BRAF mutations in the tested population and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
6
0
2
Order By: Relevance
“…MM is a catastrophic skin cancer with aggressive biological actions, resistance to chemotherapy, and poor results (2). MM has a complex progress and it is hard to fully elucidate the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MM is a catastrophic skin cancer with aggressive biological actions, resistance to chemotherapy, and poor results (2). MM has a complex progress and it is hard to fully elucidate the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, MM accounted for 60–80% of skin-cancer related deaths (1). Recent studies have indicated that MM is not a single entity but a set of various kinds of neoplasms with different causes, biological behaviors, and outcomes (2). Unfortunately, despite the development of technology and medicine, the survival rate for advanced MM has not improved significantly in the past eight years (3).…”
Section: Introductionmentioning
confidence: 99%
“…Malignant melanoma is the most aggressive tumour of the skin, which arises from the transformation of melanocytes. Its incidence has increased significantly in the last decades [1]. Over the past few years thanks to the development of immunotherapy with immune checkpoint inhibitors and targeted therapy against kinases of the RAS/BRAF/MAPK pathway, the clinical outcome has improved dramatically with the achievement of long term benefit in approximately 50% of patients with metastatic disease [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that its incidence in PLWH is 2.6 times higher than in those uninfected (Marra et al, 2017). This increased incidence is due both to the reduced efficacy of the host immune response in eliminating potentially malignant cells and to the increased survival of PLWH after the introduction of HAART (Ryška et al, 2017). Moreover, in HIVinfected people, melanoma has generally a more aggressive behavior and lower survival compared to uninfected people (Coghill, Shiels, Suneja, & Engels, 2015).…”
Section: Risk Of Malignant Melanoma In Hiv-infected Peoplementioning
confidence: 99%